Calcitriol inhibits osteoclastogenesis in an inflammatory environment by changing the proportion and function of T helper cell subsets (Th2/Th17). (13th May 2020) - Bi, Chun‐Sheng; Li, Xuan; Qu, Hong‐Lei; Sun, Li‐Juan; An, Ying; Hong, Yong‐Long; Tian, Bei‐Min; Chen, Fa‐Ming
Abstract: Objectives: Previously, we found that by regulating T helper (Th) cell polarization, calcitriol intervention inhibited lipopolysaccharide (LPS)‐induced alveolar bone loss in an animal periodontitis model, but the underlying cellular events remain unknown. Materials and methods: In this study, mouse Th cells were incubated in an inflammatory environment in the presence of dendritic cells (DCs) and LPS. Then, the potential of the Th cells to undergo Th2/Th17 polarization, the RANKL expression of the polarized Th cells and the subsequent influences of the polarized Th cells on RAW264.7 cell osteoclastogenesis in response to calcitriol administration were assessed. Finally, the effects of calcitriol on antigen presentation by DCs during these cellular events were evaluated. Results: In response to calcitriol administration, Th cells in an inflammatory environment exhibited an enhanced potential for Th2 polarization along with a decreased potential for Th17 polarization. In addition, RANKL expression in Th17‐polarized cells was largely inhibited. Furthermore, inflammation‐induced osteoclastogenesis in RAW264.7 cells was suppressed following coculture with calcitriol‐treated Th cells. During these cellular events, increased expression of Th2 promoters (such as OX‐40L and CCL17) and decreased expression of Th17 promoters (such as IL‐23 and IL‐6) were found in DCs. Conclusions: Calcitriol can inhibit osteoclastogenesis in an inflammatory environment by changing the proportion and function of Th cell subsets. Our findings suggest that calcitriol may be an effective therapeutic agent for treating periodontitis.